1994
DOI: 10.1159/000236657
|View full text |Cite
|
Sign up to set email alerts
|

lnterleukin-6 Production by Draining Lymph Node Cells following Primary Contact Sensitisation of Mice: Relationship to the Proliferative Response

Abstract: Interleukin-6 (IL-6) production and proliferative responses by draining lymph node cells were studied in mice exposed topically to a series of chemicals. Chemicals with the capacity to induce sensitisation, but not non-sensitisers, promoted both IL-6 production and lymph node cell proliferation ex vivo. The responses exhibited similar kinetics, were dependent upon the dose of topically applied allergen, and correlated significantly. We demonstrate that the main source of IL-6 within draining lymph nodes is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…The latter accords with our observation that proliferation and IL-6 production by LNCs are highly correlated (Hope, Dearman, Debicki, et al, 1994). Initially, we determined the proliferation of draining LNCs in response to application of antigens to the skin of Syrian hamsters.…”
Section: Discussionsupporting
confidence: 83%
“…The latter accords with our observation that proliferation and IL-6 production by LNCs are highly correlated (Hope, Dearman, Debicki, et al, 1994). Initially, we determined the proliferation of draining LNCs in response to application of antigens to the skin of Syrian hamsters.…”
Section: Discussionsupporting
confidence: 83%
“…In line with data from local lymph node assays in mice (Hope et al 1994b) and rats (Arts et al 1996), an increase in DLN cell numbers and ex vivo proliferation, the immunological correlates of hapten's contact-sensitizing potential, was noted in rats sensitized with DNCB. Higher DLN cellularity in sensitized, as compared to non-sensitized rats might be a consequence of cell migration to lymph nodes and/or cell proliferation.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, some investigators have reported that retinoids modulate the production of cytokines such as IL-6 [5], IL-4 [6] and IFN-Á [7] at the transcriptional level. Retinoid is a potent ligand for retinoic acid receptors (RARs), which belong to the steroid/thyroid receptor superfamily [8].…”
Section: Introductionmentioning
confidence: 99%